(untitled) (Journal of English Language Teaching Development, 2024)
The study aimed to observe the public speaking proficiency and classified the speech anxiety levels of students based on the causal factors of speech anxiety related to communication apprehension, low of self-confidence, and fear of negative evaluation factors. The research utilized a descriptive-qualitative method. The respondents were 35 students at the 11th grade of SMAN 1 Kaledupa, Wakatobi Regency in academic year of 2022/2023. The research data collection used Foreign Language Speaking Anxiety Scale (FLSAS) Questionnaire. The data were classified by using Likert Scale. The findings indicated that 30 from 35 students were classified into moderate level category and there were 5 students classified into low level category. The research found several linguistic and non-linguistic aspects related to the three main causal factors: fright stage, learning disability (lack of vocabulary, grammatical rules, and pronunciation difficulties), lack of-preparation, low of self-motivation, and uncomfortable when speaking English as the substantial items that influenced speech anxiety when performing public speaking in front of audience.